Investment Portfolio Optimization of Mean-Entropic-VaR Model on the Top Ten Stocks from LQ45 in the Indonesian Capital Market - Nurnisaa binti Abdullah Suhaimi; Herlina Napitupulu; Sukono Sukono (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
In an investment portfolio, investors certainly choose a portfolio according to their preferences for return and risk. The problem is the allocation of investment weights in forming a portfolio, if the risk is in the form of Entropic-Value-at-Risk (EVaR). The purpose of this study is to determine the allocation of investment weights that maximize returns and minimize portfolio risk. The method used in this study is through investment portfolio optimization in the form of Mean-EVaR. The stages carried out are selecting the ten best stocks in the LQ45 index, estimating and testing the suitability of the return distribution, determining expectations, variance and covariance between stock returns, and optimizing the allocation of investment portfolio weights using the Mean-EVaR model. Based on the results of the analysis, it was obtained that the optimal portfolio weight allocation is 0.01073, 0.23284, 0.04617, 0.08052, 0.00470, 0.09021, 0.14669, 0.00427, 0.22672 and 0.15715, to be allocated successively to the stocks ACES, BBRI, EXCEL, ITMG, PTBA, ADRO, BBTN, GGRM, KLBF and AKRA. In this optimal portfolio, the average portfolio return is obtained at 0.00055 with an EVaR risk of 0.01632. It is hoped that the results of this study can provide a significant contribution to investors in making investments, especially in the ten stocks analyzed.